Electronic Media Pillar of Learning Evaluation in Madrasah - Ahmad Zainuri; Saepuloh Saepuloh (Nazhruna: Jurnal Pendidikan Islam, 2022)
The purpose of the study was to determine the process of implementing the e-learning system at MIN 1 Ogan Ilir and how to implement the evaluation of learning through e-learning. This study uses a descriptive qualitative approach. Data collection techniques include interviews, observation, and documentation. Data analysis techniques include data collection, data reduction, data presentation, conclusion drawing, and verification. The result of the research is that the implementation of learning evaluation through e-learning at MIN 1 Ogan Ilir succeeded in creating more efficient and flexible learning. This is based on indicators of the success of the e-learning system, one of which is that e-learning can overcome time constraints and is flexible. The benefit for the field of science in this research is as consideration for implementing an e-learning system in the evaluation of learning so that it is more effective and on target.